LITERASI INFORMASI PETANI NANAS DALAM MENINGKATKAN PRODUKTIVITAS PERTANIAN DI DESA TANGKIT BARU KEC. SUNGAI GELAM KAB. MUARO JAMBI - Andi Junudu; Muhammad Rum; Wenny Dastina (Nazharat: Jurnal Kebudayaan, 2020)
This article discusses the pineapple farmer’s literacy in improving agricultural productivity in the Tangkit Baru Village. The Purpose of this article was to explore the literacy level of farmer information by default of The International Federation of Library Association and Literacy (IFLA). The writing employed a descriptive qualitative method with a sampling approach. The data analysis technique used is the flow model of data reduction, data presentation and deduction scheme. The results proved that the pineapple farmers’ literacy in the village of Tangkit Baru in good category, with increased productivity. The default IFLA information literation component suggest, (information access) is obtained through socialization among farmers, as well as through generations; then at the rate (information evaluation), farmers know the variety of plants, the inhibitory factors dof locating information, and the ability to compare the information accordingly are evaluated so that information can be useful; and (use of information), farmers apply information through experimentation and information obtained, disseminated and communicated to create coexistence. The pineapple farmers in the Tangkit Baru village at the average level of secondary school are able to work well, because of the important information literacy role of their communities. Which, of course, the pineapple productivity will increase as well as minimize the damage to the farmland.